2002
DOI: 10.1021/jp0121365
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Rate Constants for Collisional Vibrational Relaxation in Dense Vibrational Regions of S1 p-Difluorobenzene

Abstract: To gain insight into the possible magnitude of vibrational activation/deactivation rate constants for large molecules with the high vibrational excitation of thermal unimolecular reactions, absolute vibrational relaxation rate constants have been measured in S1 p-difluorobenzene energy regions where the vibrational levels begin to form a quasi-continuum. The measured rate constants define vibrational energy transfer from three initially pumped S1 levels into the surrounding vibrational field. The observed rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…We are using O 2 fluorescence quenching as part of a study of collisional vibrational energy transfer from regions of the vibrational manifold with high state densities. 7 In support of the study, we report here a reinvestigation of O 2 fluorescence quenching kinetics designed to gain an understanding of why deviation from the standard Stern-Volmer model occurs. Quenching of S 1 pDFB fluorescence has been characterized over a pressure range spanning more than 4 orders of magnitude, starting with O 2 pressures below one Torr where, on average, less than one hard-sphere collision occurs during the fluorescence lifetime.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…We are using O 2 fluorescence quenching as part of a study of collisional vibrational energy transfer from regions of the vibrational manifold with high state densities. 7 In support of the study, we report here a reinvestigation of O 2 fluorescence quenching kinetics designed to gain an understanding of why deviation from the standard Stern-Volmer model occurs. Quenching of S 1 pDFB fluorescence has been characterized over a pressure range spanning more than 4 orders of magnitude, starting with O 2 pressures below one Torr where, on average, less than one hard-sphere collision occurs during the fluorescence lifetime.…”
Section: Introductionmentioning
confidence: 70%
“…We are using O 2 fluorescence quenching as part of a study of collisional vibrational energy transfer from regions of the vibrational manifold with high state densities . In support of the study, we report here a reinvestigation of O 2 fluorescence quenching kinetics designed to gain an understanding of why deviation from the standard Stern−Volmer model occurs.…”
Section: Introductionmentioning
confidence: 77%
“…Most studies of collisional dynamics of electronically excited species have focused on measuring quenching rates of excited molecules in thermal samples. Spectroscopic resolution of fluorescence from the excited state has allowed detailed study of rotational and vibrational energy transfer in small and large molecular systems [4][5][6][7][8][9]. Such fluorescence-based measurements of NO(A 2 AE þ ) collisional quenching have also served as useful quantitative diagnostics of chemistry at high pressures [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Our focus here is on vibrational relaxation rates, and several experiments have demonstrated that the hard sphere potential is not always appropriate. 24,[28][29][30][31] The Lennard-Jones (6, 12) potential has been demonstrated to contain the essential features required to model various trends in observed vibrational relaxation rates. [32][33][34][35][36][37][38][39] The Lennard-Jones cross section σ LJ is related to the hard sphere cross section via the omega integral, Ω (2,2)* :…”
Section: Theorymentioning
confidence: 99%
“…The calculated collision rate is sensitive to the choice of intermolecular potential and hence σ . Our focus here is on vibrational relaxation rates, and several experiments have demonstrated that the hard sphere potential is not always appropriate. ,− The Lennard-Jones (6, 12) potential has been demonstrated to contain the essential features required to model various trends in observed vibrational relaxation rates. The Lennard-Jones cross section σ LJ is related to the hard sphere cross section via the omega integral, Ω (2,2)* : where Ω (2,2)* contains the temperature dependence of σ LJ . The choice of Ω (2,2)* over other Ω ( l , s )* integrals is to some extent arbitrary, but there is a precedent for its use. In any case, the difference between the various forms of the Ω ( l , s )* integrals is slight…”
Section: Theorymentioning
confidence: 99%